2008
DOI: 10.1002/kin.20360
|View full text |Cite
|
Sign up to set email alerts
|

The role of Ni(II) in the oxidation of glycylglycine dipeptide by peroxomonosulfatex

Abstract: The kinetics of oxidation of the dipeptide glycylglycine by peroxomonosulfate (PMS) was studied in the pH range of 3.42-5.89. The rate is first order in [PMS], glycylglycine concentration, and inverse first order in [H + ]. The kinetic data suggest that SO 2− 5 reacts, with glycylglycine, faster than H SO − 5 by five orders of magnitude. The observed kinetics can be explained as due to the formation of an intermediate by the nucleophilic interaction of peroxide with the terminal protonated amine of glycylglyci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Similar results were observed in the decomposition of PMS in the presence of Ni(II) at acidic pH [15] as well as in the oxidation of Ni-glycylglycine [16]. By analogy with the earlier studies we can assume the oxidation of glycolates proceeds through a molecular mechanism.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Similar results were observed in the decomposition of PMS in the presence of Ni(II) at acidic pH [15] as well as in the oxidation of Ni-glycylglycine [16]. By analogy with the earlier studies we can assume the oxidation of glycolates proceeds through a molecular mechanism.…”
Section: Resultssupporting
confidence: 83%
“…However, results from this laboratory show that Ni(II) ion catalyzed decomposition of PMS in acidic pH [15] proceeds through the oxygen atom transfer mechanism with nickel peroxide intermediate instead of redox mechanism. The oxidation of Ni-glycylglycine by PMS also involves an oxygen atom transfer mechanism [16]. Therefore, in continuation of exploring the possibility of Ni(II)-PMS system without redox process, we have studied the reaction of GLYCA with PMS in the presence of Ni(II) and Cu(II) and the results are reported.…”
Section: −•mentioning
confidence: 98%
“…MR was used as a drug-model, based on its medium-strong association constant with βCD (k a around 5 • 10 3 M À 1 ) and the direct visual information. [54][55][56] Biphasic systems have proven to be very illustrative to study supramolecular interactions involving hydrophobic/hydrophilic building blocks via phase transfer. [57] In a biphasic system based on water and dichloromethane (DCM), MR resides mainly in the DCM layer, due to its hydrophobicity.…”
Section: Encapsulation and Release Of Methyl Red Dyementioning
confidence: 99%
“…The peak shift from 420 nm to 520 nm is related to the pH and the MR protonation. [54,56] Figure S27 shows an increase in the absorbance of the dye when it is encapsulated inside the cyclodextrin. This effect is related to the transfer of the guest from a more protic Figure 4.…”
Section: Encapsulation and Release Of Methyl Red Dyementioning
confidence: 99%
“…The kinetic results revealed that silver catalyzed reaction occurred approximately 10 4 times faster than the uncatalyzed reaction and this is attributed to the formation of (adduct) 2+ . The bimolecular rate constant (k) for the slow step and the activation parameters were calculated and the results are discussed.Ó 2009 Elsevier B.V. All rights reserved.Oxidation of amino acids (AA) by peroxomonosulphate in acidic, basic and neutral media in the absence and in the presence of transition metal ions has been extensively studied by many researchers [1][2][3][4][5][6][7][8][9][10]. This apparently mimics the mechanism of biological oxidation of amino acids proceeding through formation of Schiff base intermediate with pyridoxal phosphate in living systems.…”
mentioning
confidence: 99%